guiding the teacher role to the social phenomenon: child abuse (Revista Electrónica REDINE, 2018)
This research descriptive character field, aimed to analyze the guiding role of the teacher to the child abuse social phenomenon, demonstrated among children in different educational institutions of Lara state. To determine the existing phenomenon quantitative descriptive field research was conducted, while a type rating scale instrument whose purpose was to determine the need for teachers to acquire tools that enable them to detect and channel scenarios applied of child abuse. After obtaining the results applied to twenty (20) teaching questionnaire, an analysis and interpretation of the results to finally establish a series of conclusions and recommendations that I aspire to be a contribution it was made allowing not only educators, but also Representatives face the parents and child abuse social phenomenon, which has been accentuated in recent years.
Keywords: teaching; guiding role; social phenomenon; child abuse